The Development of Finite Element Model to Investigate the Structural Performance of Reinforced Concrete Hollow Beams - Jen Hua Ling; Lin Li Chan; Wen Kam Leong; How Teck Sia (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2020)
The self-weight of a reinforced concrete beam contributes to the permanent loads of a structure. This can be reduced by creating a longitudinal void along the beam so that it will not affect the performance of the beam. In addition, this process can reduce the amount of building cost. Therefore, a finite element model was developed in this study with the aid of a computer program, Ansys, to investigate the behavior of the hollow beam. The model was tested for reliability by comparing the predicted results with those obtained from the experiment in terms of the load-displacement responses, mechanical properties, and parametric responses. The result showed that the reliability of the model was questionable. The main cause of the non-reliability was the inaccurate prediction of the beam deflection by the model. The poor prediction of beam deflection led to significant variations of relevant mechanical properties including stiffness, deflection, and ductility. For beam deflection, only 1/3 of the specimens were correctly predicted with a reliability of 36% while the strength properties were discovered to have higher values as observed in the yield and the ultimate strengths with 73% and 64% respectively. However, both the model and experimental results showed the hollow beam was relatively effective when the diameter of the longitudinal void was 1/3 times the beam width and placed at the neutral axis. For the evaluation to improve the reliability, some revision including the properties of the materials, boundary conditions of the beam support, bonding conditions between different materials, and meshing shape and size suppose to be applied to the model.